PENGEMBANGAN MEDIA PUZZLE BOOK PADA MATERI RANTAI MAKANAN UNTUK SISWA KELAS III SEKOLAH DASAR - Wardani, Aprilia Budi; Sri Sumartiningsih; Harianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a puzzle book learning media on the topic of food chains for third-grade elementary school students and to determine the feasibility of the developed media. This research employed a Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included third-grade students of SD Negeri Kataan, a classroom teacher, and validators consisting of a material expert and a media expert. Data collection techniques were conducted through observation, interviews, questionnaires, and documentation. The results showed that the developed puzzle book media obtained a feasibility percentage of 84% from the material expert and 90% from the media expert, with an overall average of 87%, categorized as very feasible. The trial results indicated a student response percentage of 81%, also categorized as very feasible, along with an improvement in students’ learning outcomes based on the comparison of pre-test and post-test scores. Additionally, the teacher’s evaluation showed a percentage of 94%, categorized as very feasible.Thus, the developed puzzle book media is considered feasible to be used as a learning medium and is able to enhance students’ engagement and understanding of food chain concepts.